Work-integrated learning in the 21st century : global perspectives on the future - Bowen, Tracey; Drysdale, Maureen T. B. (Bingley, U.K. : Emerald Publishing Limited, 2017)
Work-Integrated Learning in the 21st century: Global perspectives on the future, explores new questions about the state of work for new university and college graduates in the context of Work-Integrated Learning (WIL). As these'Millennials' graduate, they are entering a precarious labour market that is filled with ambiguity and uncertainty, creating a great deal of anxiety for those trying to develop skills for highly competitive jobs or jobs that do not yet exist. In their pursuit of skill acquisition, many are participating in WIL programs (e.g., cooperative education, internships) which allow them to gain practical experience while pursuing their education. With a focus on WIL, this book examines issues involved in developing work ready graduates. Topics include mental health and well-being - an urgent matter on many campuses; remote working - an aspect of the information and social media age that is becoming more prevalent as the precarity of work increases; issues of diversity and discrimination; ethics and professionalism; global citizenship and competency; and the role that higher education institutions need to play to prepare students for the challenges of economic shifts. These topics are timely and relevant to the situations faced by new graduates and those who prepare them for the world beyond school. The chapters provide a close examination of the issues from a global perspective, particularly as experiential education and work-integrated learning programs are becoming more prevalent in higher education and viewed as essential for preparing millennials for the 21st century competitive labour market.
Prelims -- Learning, work, and experience: new challenges and projections for WIL -- Affordances, impacts, and challenges of new technologies -- Work-readiness for a diverse world -- Health, wellbeing, and pathways to success -- Conclusion - Moving forward: WIL in the 21st century -- About the Authors -- Index.
Includes index.
Includes bibliographical references.
Keywords: College graduates -- Employment; Experiential learning; Education -- Organizations & Institutions; Educational strategies & policy